2007
DOI: 10.2320/matertrans.48.293
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Ceramic Surface Modification of β-Type Ti-Nb-Ta-Zr System Alloy by Alkali Solution Treatment

Abstract: Biomedical -type titanium alloys have been developed or are under development all over the world. In particular, researchers in Japan have been developed Ti-29Nb-13Ta-4.6Zr alloy (TNTZ)--type titanium alloy-for biomedical applications. Bioactive ceramic surface modification is effective for further improvement in the biocompatibility of TNTZ. Calcium phosphate ceramics such as hydroxyapatite (Ca 10 (PO 4 ) 6 OH 2 ; HAP), -calcium pyrophosphate (-Ca 2 P 2 O 7 ; CPP), and -tricalcium phosphate (-Ca 3 (PO 4 ) 2 ;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The Ti-29Nb-13Ta-4.6Zr alloy appears to be promising for orthopaedic applications due its to acceptable cytotoxicity and low Young's modulus of 60 GPa [2]. It was reported that the functionality of the latter alloy can be improved by bioactive ceramic surface modification using alkali treatment [6]. The mechanical properties of Ti alloys can be tailored by compositional variation, thermomechanical processing and microstructure control.…”
Section: Introductionmentioning
confidence: 98%
“…The Ti-29Nb-13Ta-4.6Zr alloy appears to be promising for orthopaedic applications due its to acceptable cytotoxicity and low Young's modulus of 60 GPa [2]. It was reported that the functionality of the latter alloy can be improved by bioactive ceramic surface modification using alkali treatment [6]. The mechanical properties of Ti alloys can be tailored by compositional variation, thermomechanical processing and microstructure control.…”
Section: Introductionmentioning
confidence: 98%
“…However, the HAp formability of different types of Ti alloys with various kinds and amounts of alloying elements varies after alkali treatment. The HAp formability of TNTZ is lower than that of pure Ti, 13) for example. Therefore, to improve the HAp formability on the TNTZ surface, it is important to understand the relationship between alloying elements (Nb, Ta and Zr) and the HAp formability.…”
Section: Introductionmentioning
confidence: 94%
“…When sodium tantalate is in a crystalline phase on the surface, it barely releases the Na + ions, leading to the formation of only a small number of TaOH groups on the surface and low production of HAp from ionic activity in the SBF. However, the sodium tantalate layers should be in the amorphous state, 13) suggesting that the TixTa (x = 10, 20, 30, or 40 mass%) alloys should have good HAp formability. For pure Ta, the clear and sharp peaks of Na 5 TaO 5 in the TF-XRD profile (Fig.…”
Section: Hap Precipitation In Sbfmentioning
confidence: 99%
“…There is another report 34) that the formability of HAP is less in pure Nb (CP-Nb) than in pure Ta (CP-Ta) and pure Zr (CP-Zr) as summarized in Table 2. The formability of HAP is the lowest in CP-Nb.…”
Section: Biologically and Mechanically Biocompatible Titanium Alloysmentioning
confidence: 99%